Bibliotecários e notícias falsas: Como profissionais podem contribuir no combate à desinformação - Bueno, Isabelle Rodriguez (Universidade Federal de São Carlos, 2023)
This research intends, based on a brief bibliographic review and document research, to show all the functionality, methods and teams that make up the fact-checking agencies in Brazil, through a list of characteristics (checklist), with ten components to be analyzed in order to make a brief reflection on how the professional librarian can contribute to the fight against misinformation. The bibliography review will first address the structure behind disinformation and information pollution, and will make a brief history of journalistic types based on Weberian methodology. The result of the research shows that there are not, in the four analyzed agencies, Librarianship and Information Science professionals present, being these mostly composed of journalists, computer scientists, publicity and propaganda, letters and social communication, and raises a series of reflections why, even with the knowledge possible to identify informational processes and flows, there are still no information scientists contributing to fact-checking agencies.
Librarians and fake news: How professionals can help combat disinformation
Keywords: Fact checking; Disinformation; Fake news; Desinformação; Notícias falsas; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::PROCESSOS DE DISSEMINACAO DA INFORMACAO